The moderating effect of income diversification on intellectual capital and company performance: Case study of banking in Indonesia - Wahyuningtias, Eko; Kusumawardhani, Ratih (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Purpose – This research aims to examine the influence of intellectual capital on company performance, analyze the moderating effect of revenue diversification, and provide additional insight into intellectual capital.Design/methodology/approach – This research uses 38 banks in Indonesia that are listed on the Indonesia Stock Exchange (BEI) out of a total of 47 banks as research samples. The collected data was analyzed using linear regression and moderated regression analyses to test the effect of intellectual capital on company performance and the moderating impact of income diversification on intellectual capital and company performance.Findings – The results of the regression analysis show that intellectual capital (VAIC) has a positive effect on company performance. In contrast, income diversification is having a moderating impact on intellectual capital and company performance. The intellectual capital component has varying influences on company performance. Whereas VACA has a positive effect on company performance, VAHU also has a positive effect on company performance. In contrast, STVA does not affect company performance. Based on the moderation test, income diversification does not moderate the relationship between intellectual capital components and company performance.Research limitations/implications – This research uses the VAIC method to measure intellectual capital using financial report benchmarks. Future researchers should consider using new techniques that are more accurate and comprehensive in measuring intellectual capital. Thus, further research will provide a more precise picture of intellectual capital's influence in improving banking companies' performance.Practical implications – This research shows that banking activities with an intellectual capital orientation tend to improve company performance. So, it is recommended for banking companies to utilize and develop the intellectual capital they have.Originality/value – This research provides an understanding of intellectual capital. This research also contributes to developing economic theory related to intellectual capital and company performance.